2018
DOI: 10.1016/j.amepre.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Sedentary Behavior, and Retirement: The Multi-Ethnic Study of Atherosclerosis

Abstract: The retirement transition was associated with changes in physical activity and TV watching. To inform intervention development, future research is needed on the determinants of behavior change after retirement, particularly among individuals of low socioeconomic position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 51 publications
(71 reference statements)
3
39
0
Order By: Relevance
“…Our results relating retirement to LTPA engagement are similar to previous investigations using ARIC data [24,25]. The differences observed by retirement status provide further indication that retirement from work is associated with greater engagement in PA among older adults.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results relating retirement to LTPA engagement are similar to previous investigations using ARIC data [24,25]. The differences observed by retirement status provide further indication that retirement from work is associated with greater engagement in PA among older adults.…”
Section: Discussionsupporting
confidence: 88%
“…Baseline characteristics of ARIC Study participants (aged 45-64 at cohort intake) and according to cohort retention as quantified by the number of non-missing LTPA measurements over follow-up including baseline (i.e., 3, 2, or 1). African American n (%) 3971 (26) 1005 (20) 1791 (25) 1175 43<High school education n (%) 3560 (24) 644 (13) 1827 (25) 1089 (39) Not married n (%) 2849 (20) 866 (18) 1372 (19) 611 (23) Behavioral-metabolic factors Current cigarette smoking n (%) 3965 (26) 867 (17) 1991 (27) 1107 40Obesity (BMI ≥30 kg/m 2 ) n (%) 4161 (28) 1143 232133 29885 32Hypertension* n (%) 4300 (29) 1402 281987 (27) 911 33Diabetes † n (%) 1511 (10) 193 4813 (11) 505 18LTPA…”
Section: Age-related Patterns In Ltpamentioning
confidence: 99%
See 1 more Smart Citation
“… Barnett, van Sluijs, Ogilvie, and Wareham (2012) found a decline in overall PA among British retirees, but the magnitude of association was larger for men and women who retired from manual social class occupations. Jones, Li, Aiello, O’Rand, and Evenson (2018) found that total PA declined after retirement among individuals of low socioeconomic position but remained stable among those of high socioeconomic position. In this study, socioeconomic position was measured by education, household income, and wealth.…”
Section: Resultsmentioning
confidence: 93%
“…Retirement was the most examined life transition with 29 studies (27.1%). In general, retirement was associated with increases in leisure-time PA, (recreational) walking, and domestic activities [40,84,85,87,88,90,91,93,96,99,100,103,104,[106][107][108][109]132] and decreases in occupational PA, active transportation, and total PA [83,84,93,103,104,106,107]. With regard to PA intensities, an increase especially in light and moderate PA occurred [87,96], whereas findings on vigorous and moderate-to-vigorous PA were more ambiguous [93, 95, 96, PLOS ONE 105,132].…”
Section: Employment-related Events and Transitionsmentioning
confidence: 93%